JURIDICAL ANALYSIS OF THE VALIDITY OF DEEDS READ WITHOUT THE PRESENCE OF A NOTARY IN NOTARIAL PRACTICE IN BATAM CITY - Giofanny Marchellino Fransiscus Tulung; Erniyanti; Soerya Respationo; Markus Gunawan; Mania (Journal of International Islamic Law, Human Right and Public Policy, 2026)
A notarial deed is an authentic deed that possesses full evidentiary power and serves to provide legal certainty for parties in a variety of civil legal relationships. The authenticity of a notarial deed is determined not only by the authority of the notary as a public official, but also by the fulfillment of formal and material requirements as regulated in the Civil Code and the Law on the Office of Notary. In notarial practice, indications still arise of deed readings conducted without the presence of the notary or delegated to notary office staff. Such conditions have the potential to give rise to issues concerning the validity of the deed, its evidentiary strength, and the legal responsibility of the notary. This study aims to analyze the legal provisions regarding the validity of deeds read aloud without the presence of a notary, examine their impact on notarial practice in Batam City, and identify the legal risks arising for the deed, the parties involved, and the notary. This study employs a normative-empirical legal research method with statutory, conceptual, and empirical approaches. Data were obtained through literature review, document study, and interviews with notaries, the Notary Supervisory Council, and relevant parties in Batam City. The data obtained were analyzed using qualitative juridical analysis. The research results show that the obligation of the notary to read out the deed directly in the presence of the appearing parties is a formal requirement that must be fulfilled in the creation of an authentic deed. Reading the deed without the notary’s presence may cause the deed to lose its authenticity, weaken its evidentiary strength, and create legal uncertainty for the parties. In addition, such practice poses risks of civil, administrative, ethical, and even criminal liability for the notary if it is proven to cause loss or is done intentionally. Therefore, enhanced supervision, notary compliance with the provisions of the Notary Position Law, and legal education for the public are needed to ensure legal certainty and safeguard the integrity of the notarial profession.